Seismic reflection imaging of karst in the Persian Gulf; Implications for the characterization of carbonate reservoirs - Burberry,CM; Jackson,CA-L; Chandler,S (AAPG Bulletin, 2016)
Karstification positively and negatively affects the quality of carbonate reservoirs; for example, dissolution and brecciation can increase porosity and permeability, whereas cavern collapse or cementation driven by postkarstification fluid flow may occlude porosity and reduce permeability. Karst may also pose challenges to drilling because of the unpredictable and highly variable porosity and permeability structure of the rock and the corresponding difficulty in predicting drilling mud weight. When combined, outcrop, petrographic, and geochemical data can constrain the style, distribution, and origin of seismic-scale karst, which may provide an improved understanding of carbonate reservoir architecture and allow development of safer drilling programs. However, relatively few studies have used seismic reflection data to characterize the regional development of seismic-scale karst features. In this study we use time-migrated two-dimensional seismic reflection data to determine the distribution, scale, and genesis of karst in a 3-km-thick (9800-ft-thick), Jurassic–Miocene carbonate-dominated succession in the Persian Gulf. We map 43 seismic-scale karst features, which are expressed as vertical pipe columns of chaotic reflections capped by downward-deflected depressions that are onlapped by overlying strata. The columns are up to 2 km (6500 ft) tall, spanning the Upper Jurassic to Upper Cretaceous succession, and are up to 5.5 km (18,000 ft) in diameter. We interpret these pipes to have formed in response to hypogene karstification by fluids focused along preexisting faults, with hypogene-generated depressions enhanced by epigene processes during key intervals of exposure. Our study indicates that seismic reflection data can and should be used in conjunction with petrographic and geochemical techniques to determine the presence of hypogene karst plays and to help improve the characterization of carbonate reservoirs and associated drilling hazards.